2018
DOI: 10.1590/1807-1929/agriambi.v22n10p679-682
|View full text |Cite
|
Sign up to set email alerts
|

Water potential and gas exchanges in sugarcane irrigated with saline waters

Abstract: In Pernambuco, state in the northeastern region of Brazil, in the coastal areas, due to the intrusion of seawater, the waters used for sugarcane irrigation can have high salt contents and cause serious problems to soil and plant. The present study aimed to evaluate the effects of irrigation with saline water on the physiology of sugarcane, variety RB867515, irrigated under five salinity levels of 0.5; 2.0; 3.5; 5.0 and 6.5 dS m-1 in a completely randomized design, with four replicates in drainage lysimeters. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Thus, it is evident that the longer exposure of plants to salt stress has contributed to the intensification of deleterious effects on the growth in plant height, as verified at 107 DAS. According to Acosto-Motos et al (2017), in the long term, salt stress affects the photosynthetic process, due to the accumulation of salts in the leaves. Bezerra et al (2018) state that the decrease is a response to the reduction in the osmotic potential of the soil due to the increase in irrigation water salinity and accumulation of Cland Na + ions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is evident that the longer exposure of plants to salt stress has contributed to the intensification of deleterious effects on the growth in plant height, as verified at 107 DAS. According to Acosto-Motos et al (2017), in the long term, salt stress affects the photosynthetic process, due to the accumulation of salts in the leaves. Bezerra et al (2018) state that the decrease is a response to the reduction in the osmotic potential of the soil due to the increase in irrigation water salinity and accumulation of Cland Na + ions.…”
Section: Resultsmentioning
confidence: 99%
“…Stomatal conductance decreased linearly with the increase in irrigation water salinity (Figure 5A), with losses of 9.48% per unit increase in ECw and of 60.91% between plants irrigated with waters of 6.7 dS m -1 and 0.7 dS m -1 . The limitation in water availability in response to osmotic stress resulting from the increase in ECw restricts stomatal conductance, constituting an important strategy of plants to avoid severe dehydration and maintain high cell water potential (LIRA et al, 2018). The results (Figures 1, 2, 3 and 4) are in agreement with Marchiori et al (2017), who concluded that the changes observed in crop growth reflect a possible state of water deficit in plants and that, in this situation, it can restrict the dilution of ions such as Na + and Clin plant tissues, causing greater accumulation of these elements to the detriment of biomass, with consequent toxicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Dias et al (2020) was developed in Campina Grande -PB, Brazil, a region characterized by milder temperatures and high relative humidity. According to Lira et al (2018), the reduction in gs in response to increases in ECw is an important strategy for plants to avoid severe dehydration and maintain high cellular water potential, since osmotic stress limits water availability.…”
Section: Resultsmentioning
confidence: 99%